Geomagnetic Disturbances That Cause GICs: Investigating Their Interhemispheric Conjugacy and Control by IMF Orientation. Issue 10 (19th October 2022) - Engebretson, Mark J.; Simms, Laura E.; Pilipenko, Viacheslav A.; Bouayed, Lilia; Moldwin, Mark B.; Weygand, James M.; Hartinger, Michael D.; Xu, Zhonghua; Clauer, C. Robert; Coyle, Shane; Willer, Anna N.; Freeman, Mervyn P.; et al.
Abstract: Nearly all studies of impulsive geomagnetic disturbances (GMDs, also known as magnetic perturbation events MPEs) that can produce dangerous geomagnetically induced currents (GICs) have used data from the northern hemisphere. In this study, we investigated GMD occurrences during the first 6 months of 2016 at four magnetically conjugate high latitude station pairs using data from the Greenland West Coast magnetometer chain and from Antarctic stations in the conjugate AAL‐PIP magnetometer chain. Events for statistical analysis and four case studies were selected from Greenland/AAL‐PIP data by detecting the presence of >6 nT/s derivatives of any component of the magnetic field at any of the station pairs. For case studies, these chains were supplemented by data from the BAS‐LPM chain in Antarctica as well as Pangnirtung and South Pole in order to extend longitudinal coverage to the west. Amplitude comparisons between hemispheres showed (a) a seasonal dependence (larger in the winter hemisphere), and (b) a dependence on the sign of the By component of the interplanetary magnetic field (IMF): GMDs were larger in the north (south) when IMF By was >0 (<0). A majority of events occurred nearly simultaneously (to within ±3 min) independent of the sign of By as long as | By | ≤ 2 | Bz |. As has been found in earlier studies, IMF Bz was <0 prior to most events. When IMF data from Geotail, Themis B, and/or Themis C in the near‐Earth solar wind were used to supplement the time‐shifted OMNI IMF data, the consistency of these IMF orientations was improved. Key Points: Large (>6 nT/s) geomagnetic disturbances (GMDs) were identified in data from conjugate magnetometer arrays in Greenland and Antarctica GMD amplitudes were larger in the winter hemisphere and larger in the north (south) when interplanetary magnetic field By was >0 (<0) Minima in the Bx component of most GMDs appeared simultaneously (within 3 min) in conjugate hemispheres